ANALISIS PENGARUH PEMBERIAN KUNYIT DALAM MENGURANGI GRAVIDARUM PADA IBU HAMIL DI PUSKESMAS DOLOK MASIHOL TAHUN 2018 - LISNANI . (JURNAL ILMIAH MAKSITEK, 2020)
In assessing the degree of public health, there are several indicators that can be used. These indicators are generally reflected in conditions of morbidity, mortality and nutritional status. In this section, the degree of public health in Indonesia is described through the (MMR) Maternal Mortality Rate (Indonesia Health Profile, 2010). Gravidarum is a complaint experienced by pregnant women that interferes with daily activities, decreased appetite, causing nutritional disturbances in the fetus. gravidarum can increase the risk of pregnancy disorders. Turmeric is a herb that has long been known to prevent nausea and vomiting which contains gingerol compounds which have antiemetic activity and reduce metoclopamide compounds which can cause nausea and vomiting. The sample was 32 pregnant women in the first trimester who experienced gravidarum at Dolok Masihol Health Center as many as 32 respondents for each experimental and control group. The sampling technique used simple total sampling and the data were analyzed using paired t test. The average frequency of gravidarum in the experimental group before being given turmeric was 2.38 times / day decreased to 1.00 times / day. Therefore, there are significant differences before and after giving turmeric. The difference in the average emesis gravidarum frequency before and after the experimental group was a decrease in the emesis gravidarum frequency, while in the control group it was 0,000. Pregnant women can use turmeric as an alternative medicine because it is cheap, easy to obtain and affordable for everyone before using antiemetic drugs, which can be processed into other variants to reduce the frequency of emesis gravidarum.